Household Water Insecurity in the Global North: A Study of Rural and Periurban Settlements on the Texas–Mexico Border. Issue 1 (2nd January 2016) - Jepson, Wendy; Vandewalle, Emily
Abstract : This article examines household-level characteristics that predict water insecurity in low-income rural and periurban communities on the Texas–Mexico border. We employ two logistic regression models (binary and ordered) to identify household characteristics that are more likely to result in water insecurity. Our analyses yielded unexpected findings: Whereas socioeconomic factors are weak predictors, immigration status of household members is a significant variable that contributes to household water insecurity. Policymakers need to pay more attention to marginalized communities as "universal" water access still leaves populations without adequate, reliable, and affordable water in the Global North.